Influence of Second-Trimester Ultrasound Markers for Down Syndrome in Pregnant Women of Advanced Maternal Age - Mariza Rumi Kataguiri; Edward Araujo Júnior; Luiz Claudio Silva Bussamra; Luciano Marcondes Machado Nardozza; Antonio Fernandes Moron (Journal of Pregnancy)
The objective of the present study was to evaluate the influence of second-trimester ultrasound markers on the incidence of Down syndrome among pregnant women of advanced maternal age. This was a retrospective cohort study on 889 singleton pregnancies between the 14th and 30th weeks, with maternal age ≥ 35 years, which would undergo genetic amniocentesis. The second-trimester ultrasound assessed the following markers: increased nuchal fold thickness, cardiac hyperechogenic focus, mild ventriculomegaly, choroid plexus cysts, uni- or bilateral renal pyelectasis, intestinal hyperechogenicity, single umbilical artery, short femur and humerus length, hand/foot alterations, structural fetal malformation, and congenital heart disease. To investigate differences between the groups with and without markers, nonparametric tests consisting of the chi-square test or Fisher’s exact test were used. Moreover, odds ratios with their respective 95% confidence intervals were calculated. Out of the 889 pregnant women, 131 (17.3%) presented markers and 758 (82.7%) did not present markers on the second-trimester ultrasound. Increased nuchal fold (P<0.001) and structural malformation (P<0.001) were the markers most associated with Down syndrome. The presence of one marker increased the relative risk 10.5-fold, while the presence of two or more markers increased the risk 13.5-fold. The presence of markers on the second-trimester ultrasound, especially thickened nuchal fold and structural malformation, increased the risk of Down syndrome among pregnant women with advanced maternal age.